Innovation in Africa : fuelling an entrepreneurial ecosystem for growth and prosperity - Umurhohwo, Deseye (Abingdon, Oxon ; New York, NY : Routledge, 2021)
This book emphasizes the need for promoting innovation on the African continent. It identifies the roadblocks for entrepreneurs and discusses ways for developing an ecosystem for innovators to pave a way through the barriers and create ground-breaking products and new technologies which meet consumers' needs in Africa. In order to stimulate innovation in African countries, there is the need for a more appropriate approach for innovation to occur in a context of international openness to knowledge. This book adopts a practical approach, demonstrating how innovation is an important driver of economic growth and competitiveness. It shows that innovation in Africa should be driven by local people, in response to local problems, and that open technology and knowledge sharing are vital to this project. It further explores key enablers such as the discovery of innovative talent, overcoming barriers, building strategic partnerships and promoting innovation across the continent. The book places emphasis on the creation of an innovation ecosystem as a value-creating tool by stakeholders for nation building and growth in Africa. This book will be of interest to researchers, students, international agencies, governments, businesses and individuals interested in the field of innovation and its potentials. It will also be relevant to investors, manufacturers and other stakeholders involved in the economic development of Africa.
OCLC-licensed vendor bibliographic record.
Keywords: Diffusion of innovations -- Africa; Economic development -- Africa; Africa -- Economic conditions -- 1960-; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Development / Economic Development